Modul Elektronik Berbasis Android Materi Perubahan Iklim Terintegrasi Nilai-nilai Islam - Septi Budi Sartika; Supriyadi Supriyadi; Akbar Wiguna (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
To strengthen Islamic values, it is best through AIK lessons and habituation, but it also needs to be integrated with other subjects, one of which is science. Science material can be integrated with Islamic values, one of which is climate change material. To make it easier to understand this material, it is necessary to develop an electronic media. This study aims to develop an android-based electronic module that is integrated with valid, practical, and effective material on climate change and Islamic values for class VII at SMP/MTs Muhammadiyah in Sidoarjo. The research method is Research and Development with the Plomp model. Data collection techniques using observation, documentation studies and Focus Group Discussion. The results showed that the results of the validity test of the Android-based electronic module were 3.57, the results of the practicality test of >75% were said to be reliable, while the results of the effectiveness test, namely the student response was very good >75%, which made the proportion of student learning outcomes in the high category 54.05% in the trial. area and 88% in limited trials in class VII A while in class VII B it is 80% and 45.95% in the medium category in wide trials and 12% in limited trials in class VII A while in class VII B it is 20% . This means that the Android-based electronic module is valid, practical and effective, climate change material is integrated with Islamic values so it is feasible to use.